Implementasi Program Pelita Berbasis Training of Trainer untuk Pengembangan Desa Cerdas Pertanian di Desa Benteng - Muhamad Dodi Bokasa; Sagita Salsabila; Muhammad Rizki Abdurrahman; Siti Anggi; Ahyar Ismail (Institut Pertanian Bogor, 2024)
Education is Indonesia's most potential investment in optimizing human resources (HR) quality. The proliferation of school dropout rates has become an educational problem in some areas of Indonesia, including Benteng Village. According to the Precision Data of Benteng Village Monograph, in 2020, 316 people, or 4.29% of the population, were classified as school dropouts. This condition causes the community to have limited skills, preventing them from maximizing the potential resources available. Therefore, preventive measures are needed to address this issue. The presence of the Agricultural Literacy Corner (PELITA) becomes a holistic and adaptive solution for the government and other stakeholders in empowering the community. This initiative aims to create upskilling, reskilling, and newskilling for the community to utilize existing agricultural resources and create a sustainable, intelligent agricultural village. Activities are implemented through socialization, counseling, training, and practice based on the ToT (Training of Trainer) scheme. The achievement of the activities can be seen from the results of the pre-test and post-test dissemination analyzed using statistical tests. The results show an increase from the pre-test score (M=2.25) to the post-test score (M=7.95). This is supported by a p-value of 0.000 < 0.001, indicating that the increase is not coincidental and has statistical significance. Therefore, the actualization of PELITA is expected to continue continuously.